2011
DOI: 10.1002/ca.21194
|View full text |Cite
|
Sign up to set email alerts
|

The lymphatic system: A historical perspective

Abstract: The study of the lymphatic system has a lengthy history, with many notable medical minds making important contributions. We now appreciate that this system is an essential component of the immune system, as well as vital to the maintenance of fluid homeostasis within the body. A good knowledge of the lymphatic system is clinically important concerning cancer, edema, surgery, and the immune response. This article reviews the history of the evolution and discovery of the lymphatic system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 24 publications
0
47
0
6
Order By: Relevance
“…Lymphatic vessels have recently been described in the meninges surrounding the mouse brain, 18 but the brain parenchyma itself is devoid of such vessels, leading to the long-held assumption that CSF serves as a ‘lymph equivalent’ to clear waste from the CNS. 74,75 Apart from transport across the endothelium, the removal of ISF from the brain parenchyma was traditionally believed to occur by diffusion 76 or ISF bulk flow into the CSF sink, which comprises the ventricles and subarachnoid space. 77 Given that diffusion is dependent on molecular size, diffusion into the CSF sink has been proposed to be too slow for the highly metabolic and large human brain.…”
Section: Clearance Systemsmentioning
confidence: 99%
“…Lymphatic vessels have recently been described in the meninges surrounding the mouse brain, 18 but the brain parenchyma itself is devoid of such vessels, leading to the long-held assumption that CSF serves as a ‘lymph equivalent’ to clear waste from the CNS. 74,75 Apart from transport across the endothelium, the removal of ISF from the brain parenchyma was traditionally believed to occur by diffusion 76 or ISF bulk flow into the CSF sink, which comprises the ventricles and subarachnoid space. 77 Given that diffusion is dependent on molecular size, diffusion into the CSF sink has been proposed to be too slow for the highly metabolic and large human brain.…”
Section: Clearance Systemsmentioning
confidence: 99%
“…by Hippocrates and Aristotle. Several centuries later, the Greek physician Claudius Galen described mesenteric lymph nodes filled with chyle, or lymph consisting of emulsified fats that originates from the small intestine (623). However, during the middle ages, this knowledge was largely forgotten until 1622 when Gasaro Aselli had the serendipitous finding of “lacteal vessels” while dissecting a live dog’s abdomen.…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%
“…He went on to trace these vessels back to the gut, and observed lymphatic valves that he surmised would prevent backflow. Aselli’s work was published in 1627, after his death, at a time when William Harvey’s theory of the circulation of blood was still novel and revolutionary (28, 337, 623). Several decades later, Jean Pecquet successfully demonstrated that chyle originating from the gut travels through the cisterna chyli and thoracic duct to the right subclavian vein, debunking the popular theory at the time that chyle traveled directly from the intestine to the liver.…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%
“…Lymphatic vessels, which run in parallel with the blood vascular system, are the principal means by which tissues eliminate excess fluid and proteins. Although the density of lymph vessels generally correlates with tissue metabolic rate (4), the brain and spinal cord are curiously devoid of such a lymphatic tree. This is puzzling because the high metabolic activity of neurons predicts the need for rapid elimination of their metabolic byproducts.…”
mentioning
confidence: 99%